2019
DOI: 10.1155/2019/5832105
|View full text |Cite
|
Sign up to set email alerts
|

Siwu Granules and Erythropoietin Synergistically Ameliorated Anemia in Adenine-Induced Chronic Renal Failure Rats

Abstract: Objective. Renal anemia in patients with end-stage chronic kidney disease is closely related to the deterioration of cardiac function, renal function, and quality of life. This study involved adenine-induced renal anemic rat models and evaluated the treatment effect of Siwu granules and/or erythropoietin (EPO). Methods. Fifty SD rats were randomly divided into 5 groups: control, model, Siwu, EPO, and Siwu plus EPO groups. The expression levels of NO, MDA, SOD, CAT, IL-6, TNF-α, EPO, EPOR, α-SMA, and TGF-β1 wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 35 publications
(37 reference statements)
1
2
0
Order By: Relevance
“…lucida was evaluated on a model of CKD using adenine. The results showed that adenine administration was associated with a reduction in GSH, CAT, and SOD supporting the findings of many other authors [ 23 , 31 , 39 ]. This reduction in the antioxidant defense mechanism was more important in the kidney than in the heart; suggesting that in this model, oxidative stress first developed in the renal tissue and secondary in the cardiac tissue.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…lucida was evaluated on a model of CKD using adenine. The results showed that adenine administration was associated with a reduction in GSH, CAT, and SOD supporting the findings of many other authors [ 23 , 31 , 39 ]. This reduction in the antioxidant defense mechanism was more important in the kidney than in the heart; suggesting that in this model, oxidative stress first developed in the renal tissue and secondary in the cardiac tissue.…”
Section: Discussionsupporting
confidence: 90%
“…Many reports have evidenced the role of oxidative stress in the pathogenesis and progression of adenine-induced CKD [ 23 , 31 ]. Therefore, the antioxidant effect of G .…”
Section: Discussionmentioning
confidence: 99%
“…After the successful preparation of the myocardial infarction model, the AMI area was divided into four points and injected with 20 µl of physiological NaCl each (a total of 80 µl) at a distance of 1-2 cm. In the LIIL group and LIILR group, IL-6 recombinant protein (1.8 mg/kg) ( 26 , 27 ) or IL-6 receptor inhibitor (50 mg/kg) ( 28 ), respectively, were accordingly injected into the four points in the myocardial infarction area.…”
Section: Methodsmentioning
confidence: 99%